Furano-(2",3",7,8)-3',5'-Dimethoxy-5-Hydroxyflavone: A New Furanoflavone from the fruits of Diospyros peregrina Gurka - Jain, Neeru; Nath Yadava, Raj (Asian Journal of Chemistry, 2010)
In the present paper we describe the isolation and structure elucidation of furano (2",3",7,8)-3´,5´-dimethoxy 5-hydroxyflavone.